Combined SARS-CoV-2 nucleic acid amplification testing and respiratory virus panel RT-PCR on the Hologic Panther Fusion system - Stevens, Bryan A. (J Clin Virol, 2021)
BACKGROUND: Significant overlap exists between the symptoms of SARS-CoV-2 and other respiratory viruses. This poses a serious challenge to clinical diagnosis, laboratory testing, and infection control programs. OBJECTIVES: To evaluate the performance of the Hologic Panther Fusion Respiratory Assays (RA) compared to the GenMark ePlex Respiratory Pathogen Panel (RPP) and to assess the ability of the Panther Fusion to perform parallel testing of SARS-CoV-2 and other respiratory viruses from a single sample. STUDY DESIGN: A diagnostic comparison study was carried out using 375 clinical nasopharyngeal specimens. Assay performance was assessed by overall, positive, and negative percent agreement and Cohen’s kappa coefficient. RESULTS: Overall agreement between the Fusion RA and ePlex RPP was 97.3 % (95 % CI 96.3−98.0), positive percent agreement was 97.2 % (95 % CI 93.0−99.2), negative percent agreement was 97.3 % (95 % CI 96.3−98.0), and the kappa coefficient was 0.85 (95 % CI 0.81−0.89). Forty additional viruses in 30 specimens were detected by Fusion that were not detected by ePlex. The maximum specimen throughput for parallel testing of the Fusion Respiratory Assays with SARS-CoV-2 was 275 samples in 20.7 h for Fusion SARS-CoV-2 and 350 samples in 20.0 h for Aptima Transcription Mediated Amplification SARS-CoV-2. CONCLUSION: Fusion RA demonstrated substantial agreement compared to the ePlex RPP. However, the Fusion detected respiratory viruses not identified by ePlex, consistent with higher clinical sensitivity. Workflows for parallel testing of respiratory pathogens and SARS-CoV-2 demonstrate that the Panther Fusion instrument provides a flexible, moderate to high throughput testing option for pandemic and seasonal respiratory viruses.